EXPLORİNG EFFECTS OF MACROECONOMİC VARİABLES ON FİNANCİAL MARKETS: EVİDENCE FROM TURKEY (Third Sector Social Economic Review, 2023)
AbstractThe entire economy of the nation and businesses both are impacted by macroeconomic factors and these factors are the main drivers of financial markets over the world. Türkiye has faced significant economic and political challenges that have affected its financial markets for a long time. After global financial crisis, Türkiye’s financial markets experienced ups and downs that brought risks for investors. This paper aims to examine the relationship between macroeconomic variables and the stock exchange index for the case of Türkiye using monthly data the period between January 2010 and December 2015. Unit root tests (Augmented Dickey-Fuller, Phillips Perron) and OLS model were applied to investigate whether macroeconomic factors such as GDP, Exchange Rate, Inflation Rate, M2, and global factors such as Crude Oil Prices, Gold Prices have an impact on ISE 100 Index, or not. The empirical findings show that Exchange Rate, M2, GDP, Gold prices, and Oil prices significantly affected the ISE 100 Index. As the results indicate, there is no evidence that the inflation rate contributes to the ISE 100 Index.
Keywords: Macroeconomic variables; ISE (Istanbul Stock Exchange); CPI (Consumer Price Index); COP (Crude Oil Prices); Exchange Rate; Türkiye